JURNALISME DAN PENGETAHUAN YANG BENAR - Rondonuwu, Sintje (Sam Ratulangi University, 2016)
ABSTRAC: Nowadays we have a beg tlord of what m call as business journalism, business of groupinternet or business of political party. Theis journalism is not in its ctrict censse a journaslism , since thejournalistic or journalism has to give the they needs of people for the real and true knowledge so that theycan arrange theirselves and grt a free life. To do this, let us learn from the cognitive psycology that teacchus that the knowletge in intelect, but he has to grew the knowledge until he has a thinking, reasoming,learning, proplem solving and decisons making. However, journalism or journakistic in cronproses has tobe based on principle and theary, and has be grounded on need and true knowladge, since in there thescientific knowledge or true knowledge has to be in growing.Key woords : Journalism, Kognotive psycology, true knoeledge